Local Soybean Development Strategy In North Sumatra - Leni Leni Handayani (JASc (Journal of Agribusiness Sciences), 2019)
The rapid import of soybeans at low prices makes the domestic soybean market dominated by imported soybeans. This makes the local soybean farmers more squeezed so that the enthusiasm of farmers to grow soybeans is reduced. The purpose of this study is how the strategy of developing local soybean agribusiness in North Sumatra. The method in this study is to use a SWOT analysis to determine the internal and external factors of soybean agribusiness conditions in North Sumatra. The SWOT analysis is carried out using a SWOT matrix and produces four alternative strategies that are able to clearly illustrate how external opportunities and threats faced by the company and its strengths and weaknesses. The results show that the strategy to increase soybean production in the study area is an aggressive strategy or SO (Strengths - Oppurtunities) strategy, which is to use strength to take advantage of existing opportunities with the following activities: (1). Utilizing Gapoktan support so farmers receive quality seed assistance and add to the experience of farmers in soybean agribusiness (2). Utilizing government support in channeling capital to expand soybean farming land. (3). Utilize average input prices and input availability to increase soybean production